THE USE OF TRANSLATION IN TEACHING READING COMPREHENSION OF DESCRIPTIVE TEXT FOR TENTH GRADE STUDENTS OF VOCATIONAL SCHOOL - Debora Julia Elisabet Damanik; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study focused on investigating the reason and analysing the process the use of translation in teaching reading descriptive text for tenth grade students at SMK Swasta Imelda Medan and SMK Swasta Jambi Medan. This study was qualitatively conducted that taken one English teacher of SMK Swasta Imelda Medan and two teachers of SMK Swasta Jambi Medan. The data were collecting by using video-recording, interviewing and observing the whole process of teaching reading descriptive text. The findings showed that the reasons of using translation in teaching reading descriptive text were facilitating communication, facilitating teacher student relationship and facilitating the learning of L2. In the process of using translation, there were 16 times of using translation found during three processes that they were conveying and checking meaning of words or sentences, explaining grammar and classroom management. It also found that the use of translation was used in the scientific approach activity that observing and questiong were the dominant used of using translation. The findings of the study revealed translation contributed to the study of foreign language teaching especially teaching reading skill.